CD137-induced apoptosis is independent of CD95 - Michel, J.; Krammer, Peter H. (Immunology, 2001)
CD95 (APO-1/Fas) and CD137 (ILA/4-1BB) are members of the tumour necrosis factor receptor family, and both are involved in induction of apoptosis in lymphocytes. Contrary to the case of CD95, apoptosis by CD137 is caused by cross-linking of the respective ligand rather than the receptor. Nothing is known so far about the mechanism of CD137-induced cell death. Here, we show that immobilized CD137 protein induces expression of CD95 in resting primary T and B lymphocytes. However, induction of apoptosis by CD137 is independent of CD95, because: (1) antagonistic anti-CD95 antibody fragments do not block CD137-induced apoptosis; and (2) CD137, but not anti-CD95, can induce apoptosis in resting lymphocytes.